2017
DOI: 10.18632/oncotarget.15628
|View full text |Cite
|
Sign up to set email alerts
|

The combination of circulating long noncoding RNAs AK001058, INHBA-AS1, MIR4435-2HG, and CEBPA-AS1 fragments in plasma serve as diagnostic markers for gastric cancer

Abstract: BackgroundSuitable diagnostic markers for cancers are urgently required in clinical practice. Long non-coding RNAs, which have been reported in many cancer types, are a potential new class of biomarkers for tumor diagnosis.ResultsFive lncRNAs, including AK001058, INHBA-AS1, MIR4435-2HG, UCA1 and CEBPA-AS1 were validated to be increased in gastric cancer tissues. Furthermore, we found that plasma level of these five lncRNAs were significantly higher in gastric cancer patients compared with normal controls. By r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 40 publications
1
77
0
Order By: Relevance
“…Notably, there is increasing evidence that combinations of several tumour markers may have improved diagnostic accuracy . Thus, we constructed different signatures by combining the plasma candidate lncRNAs into a 4‐lncRNA signature, 4 − 1 lncRNA signatures and 2‐lncRNA signatures and generated ROC curves as shown in Figures b and c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there is increasing evidence that combinations of several tumour markers may have improved diagnostic accuracy . Thus, we constructed different signatures by combining the plasma candidate lncRNAs into a 4‐lncRNA signature, 4 − 1 lncRNA signatures and 2‐lncRNA signatures and generated ROC curves as shown in Figures b and c .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there is increasing evidence that combinations of several tumour markers may have improved diagnostic accuracy. 17,18 Thus, we constructed different signatures by combining the plasma candidate lncRNAs into a 4-lncRNA signature, 4 − 1 lncRNA signatures and 2-lncRNA signatures and generated ROC curves as shown in Figures 2b and 2c. The results indicated that the combination of ZFAS1, SNHG11, LINC00909 and LINC00654, with an AUC of 0.937 (95% CI: 0.892-0.982), showed the greatest ability to differentiate CRC patients from controls in comparison with any other combination or the four lncRNAs alone.…”
Section: Evaluation Of the Crc Diagnostic Value Using Different Combimentioning
confidence: 99%
“…Indeed, researchers have identified three circulating lncRNAs, Linc00152, CFLAR-AS1, and POU3F3, as potential biomarkers for predicting the development of human esophageal squamous cell carcinoma [27]. Furthermore, levels of the circulating lncRNAs AK001058, INHBA-AS1, MIR4435-2HG, UCA1, and CEBPA-AS1 were significantly higher in gastric cancer patients compared with healthy controls [28]. However, to the best of our knowledge, no clinical studies have reported on circulating lncRNAs in OSCC to date.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, LINC00978 was reported as one of the 4 serum lncRNAs that might serve as a panel for gastric cancer diagnosis. 19 However, the biological functions and potential underlying mechanisms of LINC00978 in gastric cancer progression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al 18 found that high level of LINC00978 predicted poor prognosis in breast cancer patients. Recently, Ke et al 19 demonstrated that a combination of circulating lncRNAs including MIR4435-2HG in plasma can serve as diagnostic markers for gastric cancer. However, the precise biological function and potential underlying mechanism of LINC00978 in gastric cancer have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%